Influence of body mass index and work activity on the prevalence of median mononeuropathy at the wrist. Issue 4 (April 1997) - Werner, R A; Franzblau, A; Albers, J W; Armstrong, T J
Abstract : OBJECTIVE: To determine which proposed risk factor, work activity (industrial v clerical), body mass index (BMI), or other demographic factors had the most influence on the prevalence of median mononeuropathy at the wrist, and if there was an interaction between the risk factors. METHODS: This was a cross sectional study of active workers at five different worksites; four were industrial sites and one was clerical. 527 workers were recruited–164 clerical and 363 industrial. The presence of a median mononeuropathy in either hand was measured by electrodiagnostic techniques comparing median and ulnar sensory latencies. RESULTS: 30% of workers had an abnormality of the median sensory nerve at the wrist (34% of the industrial v 21% of the clerical workers). The adjusted risk for industrial workers was twice that of clerical workers. Obese workers (BMI > 29) were four times more likely to present with a median mononeuropathy than workers who were normal or slender (BMI < 25). There was no significant interaction between BMI and worksite in relation to median mononeuropathy. Increasing age was also related to an increased risk of median mononeuropathy. CONCLUSIONS: Obesity, industrial work, and age are independent risk factors that influence the prevalence of median mononeuropathies among active workers.